A comparative study of pine bark substrate alternatives in tobacco (Nicotina tabacum) float seedling production systems - Masaka, Johnson; Musundire, R.; Koga, C. (Academic Journals, 2021)
The present study was designed as Randomized Complete Block with three replicates, which were subjected to six treatments. Tobacco seedlings were grown in trays on float bed with treatments varying in growth media combinations as follows: T1- 50% pine bark and 50% sand (control, farmer’s present practice), T2- 100% maize cobs, T3- 100% groundnut shells, T4- 50% maize cobs and 50% sand, T5- 50% groundnut shell and 50% sand, T6- 50% groundnut shells and 50% maize. The lowest seed germination was observed in T2; T3 and T6 float trays, which, notably, did not include the sand matrix in the growth media cocktail. T2 float trays had the highest tobacco seedling mortality where a modest 58.2% germination rate was attained before rapidly dwindling to 27.3% seedling survival rate at pulling stage. The growth media without the sand component in float bed system had the lowest seedling survival percentage of a paltry 27.3%. Control float trays supported the highest tobacco seedling survival rates of 80% at transplantable stage. All growth media with sand in their combinations had relatively high germination and seedling survival rates of 68.7-80.0% (T1, T4 and T5). However, T1 and T4 quartz based seedling growth media produced comparatively higher spiral rooting rates of 1.0-2.2 and 0.8-2.3%, respectively. Growth media without sand component in T3 andT2 float trays generated the least spiral rooting rates of 0 and 0.7% at pulling stage, respectively. T2 andT4 growth media, which recorded relatively lower seedling survival counts of 27.3 and 54.2% had the heaviest shoot and root weights of 0.9 and 0.24 g; 0.89 g and 0.25 g per seedling, respectively. Growth media combinations in T1 and T3 coupled with T5 float trays, which, notably, had the highest seedling survival rates of 80.0, 68.7 and 69.5% propagated the tallest stem lengths of 159.5, 137.9 and 155.6 mm, respectively at pulling stage. In our search for alternative media combinations to the traditional pine bark/sand mix, study results suggest that the five alternative media combinations did not expose better seedling growth media qualities in almost all the essential biometric characteristics of tobacco seedlings.